KATA KETERANGAN DALAM KITAB MATIUS - HUMAMPING, NOVITA GISELA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACT This research entitled Adverbs in the book of Matthew aims to identify and classify types of adverb in three topicsÂ and to analyze position of adverbs in sentences. The method which is used in this research is descriptive method. The date are; the parable of Sower, the faith of Cannanite Woman, and the Divorce. In analyzing the data, the writer used theory of Aarts and Aarts (1982) about adverbs. Â The results of this research show that the position of adverb in the book of Matthew are; adverb before subject, adverb after subject, adverb before verb, adverb before subject attribute, and adverb after object.. Â Keywords: Advebrs, English, Analysis, Book of Matthew